Kesadaran Pajak Generasi Z: Analisis Pengaruh Sosialisasi dan Pemahaman Pajak di Kota Palembang - Evlin Pitriana; Kathryn Sugara (MDP Student Conference, 2026)
This study aims to analyze the influence of tax socialization and tax understanding on the tax awareness of Generation Z in Palembang City. The scope of the study focused on Generation Z aged 20–28 years who have income and have participated in tax socialization activities. The study used a quantitative approach with descriptive methods. The research sample consisted of 354 respondents determined through purposive sampling technique. Data were collected using a questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through SmartPLS software. The results showed that tax socialization and tax understanding have a positive and significant effect on the tax awareness of Generation Z. This finding indicates that the effectiveness of socialization and a good level of tax understanding play an important role in increasing tax awareness. This study supports the Theory of Planned Behavior in explaining the tax awareness of Generation Z.